Determinants of Green Brand Trust and the Mediating Role of Green Brand Satisfaction - Sharma, Angel; Paudel, Phadindra Kumar (The International Research Journal of Management Science, 2018)
This research attempts to examine how perceived green brand quality and perceived performance influences customers trust in green brands through enhancing brand satisfaction. Using a sample of 108 customers in Hong Kong who were observed buying green tissue products, we investigate the relationship of perceived green brand quality and perceived performance with green brand trust, and the mediating effects of green brand satisfaction on these relationships. The results show that perceived green brand quality and perceived performance positively contribute to green brand trust directly and green brand satisfaction is an effective mechanism through which perceived green brand quality and perceived performance promote trust in a green brand.